Computed tomography angiography in the diagnosis of non-ST-elevation myocardial infarction: redefining our first line of defense - Yvonne J.M. van Cauteren; Marie-Julie D.K. Lemmens; Sebastiaan C.A.M. Bekkers; Bas L.J.H. Kietselaer; Jordi Heijman; Ralph A.L.J. Theunissen; Braim Rahel; Talitha Voorn; Sander M.J. van Kuijk; Robin Nijveldt; Kevin Vernooy; Joachim E. Wildberger; et al. (International Journal of Cardiology: Heart & Vasculature)
Background: Approximately one-third of patients with suspected non-ST-elevation myocardial infarction (NSTEMI) have non-obstructive coronary artery disease. Low-risk patients might benefit from early non-invasive diagnostic testing that can appropriately select those without obstructive coronary artery disease and prevent unnecessary invasive coronary angiography (ICA). The purpose of this study is to evaluate the diagnostic value of computed tomography angiography (CTA) in suspected NSTEMI. Methods: Patients with clinically suspected type 1 NSTEMI were included. In case ICA was indicated, CTA was performed prior to ICA. The accuracy of CTA to diagnose NSTEMI, assigned by an adjudicated final diagnosis committee, was investigated. Results: Of the 66 included patients, 40 (61%) were diagnosed with NSTEMI. CAD-RADS ≥ 3 (i.e. stenosis ≥50%) had a sensitivity of 95% (95%CI 83–99%), a specificity of 65% (95%CI 44–83%) and an overall accuracy of 83% (95%CI 72–91%). The Agatston score was significantly different between patients with and without NSTEMI (404 [IQR 132–883] and 31 [IQR 0–163], respectively, p < 0.001). Nineteen patients (29%) met the criteria of ≥2 high-risk plaque (HRP) features, which was more often present in patients with NSTEMI compared to those without NSTEMI (43% and 8%, respectively, p = 0.002). Combining all CTA parameters (CAD-RADS ≥ 3, Agatston score >1.000 and ≥2 HRP features) did not improve the diagnostic accuracy compared with CAD-RADS alone. Conclusion: CTA accurately diagnoses NSTEMI in patients with acute chest pain and elevated high-sensitivity cardiac troponin T levels. Patients with NSTEMI more often presented with CAD-RADS ≥ 3, Agatston score >1.000 and HRP features.